A dual encoder network with multiscale feature fusion and multiple pooling channel spatial attention for skin scar image segmentation - Weiyuan Yang; Xiaolin Wang; Guangwei Chen; Jianming Wen; Dexing Kong; Jianfeng Zhang; Xinyang Ge; Hao Xu; Jianhua Qin (Scientific Reports)
Abstract Skin scar is a prevalent dermatological concern that impacts both aesthetic appearance and psychological well-being, making precise delineation of scar tissue essential for clinical treatment. To address the challenge of scar image segmentation, this study introduces an innovative deep learning framework integrating CNN and Swin Transformer architectures. The proposed model leverages a multi-scale feature fusion module to combine hierarchical representations from both backbones, while a novel multi-pooling channel-spatial attention mechanism enhances feature refinement during skip connections. Comprehensive experiments demonstrate the model’s superior performance in scar segmentation, achieving metrics of 96.01% Accuracy, 77.43% Precision, 90.17% Recall, 71.38% Jaccard Index, and 83.21% Dice Coefficient, which compare favorably with mainstream methods, and our model performs well in all metrics, highlighting its potential for clinical adoption in scar analysis.